Mentoring in Medicine: Introducing a structured programme in a Medical College in Delhi (Bangladesh Journal of Medical Science, 2017)
Objectives: To evaluate the response to mentoring amongst medical students after introduction of a structured mentorship programme.Methods: This was a cross sectional study conducted at Hamdard Institute of Medical Sciences and Research, [HIMSR] New Delhi. A pre validated confidential questionnaire, designed as both open and closed ended questions was utilised to obtain responses from a sample size of 300 students, both males and females. Our questionnaire solicited the following information: clarity of the concept to the mentee, duration of being involved in the programme, preferred mentoring model, comments on intended benefits and those obtained, frequency of meetings, forms of communication used and preferred place of interaction. All students in 1st, 2nd and 3rd year at HIMSR who agreed to participate in the study were included.Results: A total of 231 students returned their questionnaire, making the response rate of 77%. Different forms of communication were being used, of which personal meeting was most frequent. Both males and females were contacting their mentors in person. Majority of students preferred the mentorship model to be 1:1 and faculty members as mentors instead of senior students. Most of the students wanted the relationship to be mutual on both the sides, with both mentors and mentees having a say in the allocation process. There was no preference to gender for most of the students.Conclusions: The mentorship programme found good acceptance with medical students.Bangladesh Journal of Medical Science Vol.16(1) 2017 p.29-34